Academic propaganda in international education: detection, remedy and conceptualisation. (27th October 2021) - Shams, S.M. Riad; Thrassou, Alkis; Vrontis, Demetris; Christofi, Michael; Trichina, Eleni
Academic propaganda, as a 'darker' form of institutional brand communication strategy has been diachronically misleading target audiences for political, social and/or business purposes. Though scholars have studied the matter, primarily in its socio-political context, its business façade is under-researched. We have limited knowledge and ability in detecting academic propaganda and in developing the right antidote to it. This multidisciplinary research, thus, follows an inductive constructive approach to identify, interrelate and superimpose the critical aspects of divergent, but, related fields of cognitive communication studies, including propaganda, strategic management and marketing communication. The aim is to develop theoretical insights and propositions with regards to the detection of academic propaganda; and to construct a mechanism for its monitoring and control. We propose frameworks that theoretically contribute to the extant propaganda management literature, while practically enabling the corresponding government and non-government monitoring agencies to detect and react to academic propaganda.